Evaluation of Adrenal Reserve in Patients with Differentiated Thyroid Cancer Receiving Thyroid Hormone Suppression Therapy- case-control Comparative Study. (2nd January 2023) - Bilginer, Muhammet Cuneyt; Tam, Abbas Ali; Faki, Sevgul; Bestepe, Nagihan; Dellal, Fatma Dilek; Ozdemir, Didem; Topaloglu, Oya; Ersoy, Reyhan; Cakir, Bekir
ABSTRACT: Background: Patients with differentiated thyroid cancer (DTC) are exposed to subclinical exogenous hyperthyroidism for the suppression of thyroid-stimulating hormone (TSH). In this study, we aimed to evaluate the adrenal reserve in DTC patients receiving suppression therapy. Materials and Methods: The study included 55 DTC patients on suppression therapy and 32 healthy volunteers. Basal serum cortisol of all participants and adrenocorticotropic hormone (ACTH) of the patient group were measured. A standard-dose ACTH test (0.25 mg) was performed in patients with a basal cortisol <14.5 mcg/dL. Results: In the patient group, TSH was lower, free thyroxine (fT4) was higher, and free triiodothyronine (fT3) was similar to those of the control group (p < .01, p < .01, p = .140, respectively). The serum cortisol of the patient group was significantly lower than the control group (12.14 ± 5.12 mcg/dL vs 18.00 ± 5.56 mcg/dL, p < .001). A total of 34 (61.8%) patients with DTC had a basal cortisol <14.5 mcg/dL. Prolonged TSH suppression (≥5 years vs <5 years) was associated with lower basal cortisol (7.46 ± 2.63 mcg/dL vs 9.48 ± 2.65 mcg/dL, p = .022). The ACTH stimulation test showed that 2 (5.8%) patients had a cortisol response <18 mcg/dL. The rate of adrenal insufficiency was 3.6% in DTC patients. A moderate negative correlation was found between ACTH and fT3 of patients with low basal cortisol (r = −0.358, p = .038) Conclusion: Patients with DTC receiving TSH suppression therapy are at risk for adrenal insufficiency. The duration and severity of suppression might increase this possibility. Dynamic testing with synthetic ACTH can be used to reveal insufficient cortisol response in case of clinical suspicion.